The beauty in the Malay manuscript appreciation of art - Marzuki, Ibrahim; Mazni, Omar; Hartini, Mohd Razali; Siti Fairuz, Md Hashim (2021)
This paper aims to discuss the beautiful ornament on manuscript illumination in the Malay world. The beauty of the decorative variety in the illumination of the manuscript will be seen through the appreciation of art using the formalistic aspects of art. This study involves the study of literature through a qualitative approach to collect data from previous studies. As a result of analyzing past studies, researchers found similarities and differences in findings. In terms of similarities decorative features in the Malay manuscript illuminations highlighting the use of the gold which refers to the symbol of luxury, class, identity and style. While the similarity in terms of motifs, most use flora motifs (plants) that refer to nature as inspiration. Therefore, in terms of differences, the researchers found various findings of the study, namely the use of motifs other than flora motifs. Among other motives found in the Malay, manuscript illumination is characterized by geometric motifs, structure, symmetry, cosmology, and vegetal. Researchers also argue that the decorative style of the manuscript illumination reflects the expertise and subtlety of the manuscript decorator in revealing the natural beauty of Allah S.W.T. creation. This concept of beauty means inner beauty and external beauty (form and content).